Pengaruh Kualitas Pelayanan dan Promosi Informasi terhadap Kepuasan Masyarakat pada Kantor Imigrasi Kelas II Singaraja - Ni Putu Ayu Ika Maheswari; Made Putri Ariasih (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
Public service quality is a crucial factor in determining citizens’ satisfaction with government institutions. Immigration offices play a strategic role in providing administrative services related to travel documents and foreigner supervision, which directly affect public perceptions of government performance. This study aims to analyze the effect of service quality and information promotion on public satisfaction at the Class II Immigration Office of Singaraja. A quantitative causal-associative approach was employed, with data collected through questionnaires distributed to service users. The research variables consisted of service quality and information promotion as independent variables, and public satisfaction as the dependent variable. Data were analyzed using multiple linear regression supported by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results indicate that service quality and information promotion simultaneously have a significant effect on public satisfaction. Partially, service quality shows a significant influence with a negative direction, suggesting a gap between public expectations and perceived service performance. Meanwhile, information promotion has a positive and significant effect on public satisfaction, indicating that clear, accessible, and accurate information contributes to better public understanding of service procedures and enhances satisfaction levels. These findings imply that improving public satisfaction requires not only enhancing service performance but also strengthening communication strategies and information dissemination. The study provides both practical implications for service improvement at the Immigration Office and theoretical contributions to public service and administrative management literature.